2013
DOI: 10.1016/j.jvs.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Reserve and Stroke Risk in Patients With Carotid Stenosis or Occlusion: A Systematic Review and Meta-Analysis

Abstract: This study seems like a home run for intensive care unit patients. A simple, relatively inexpensive, and nontoxic procedure can result in a significant reduction in life-threatening bloodstream infections. Although vascular surgery patients were not specifically studied in this investigation, it seems reasonable that the results can be extrapolated to any intensive care unit patient. The authors did not detect methicillin-resistant S aureus or VRE isolates with high-level resistance to chlorhexidine during thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 0 publications
3
112
0
1
Order By: Relevance
“…Further, the optimal treatment strategy for multiple or bilateral intracranial artery stenosis remains unclear. The present two cases experienced improved vascular reserve postoperatively, which may suggest that the bypass surgery might prevent stroke to a great degree than medical treatment alone [27].…”
Section: Discussionmentioning
confidence: 57%
“…Further, the optimal treatment strategy for multiple or bilateral intracranial artery stenosis remains unclear. The present two cases experienced improved vascular reserve postoperatively, which may suggest that the bypass surgery might prevent stroke to a great degree than medical treatment alone [27].…”
Section: Discussionmentioning
confidence: 57%
“…A meta-analysis of 13 studies, which included a total of 1061 independent CVR tests in 991 patients, showed a positive association between lower CVR and future cerebral ischemic events (OR=3.86) 8. Furthermore, impaired CVR is also a known risk factor for hyperperfusion syndrome after CAS 17.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that reduced CVR is a predictor of future stroke in patients with carotid artery occlusive disease 8. These observations suggest that CVR can be used to predict periprocedural stroke in patients with CAS.…”
Section: Introductionmentioning
confidence: 95%
“…A recent meta-analysis found a significant odds ratio of 4 between impairment in CVR and subsequent risk of ischemic disease, in both symptomatic and asymptomatic carotid disease[45]. …”
Section: Clinical Impactmentioning
confidence: 99%